MODEL PERAN SERTA MASYARAKAT DALAM PENGELOLAAN RUANG TERBUKA HIJAU DI KABUPATEN BANGGAI - Risno Mina, Firmansyah Fality, Zulkifly Djanun, Syafirah Panggato (Madani Legal Review, 2022)
As the population increases, especially in the capital area of Banggai Regency, it clearly has an impact on increasing the use of space. In urban spatial planning, open space is needed to create the character of the urban community in accordance with the values of Pancasila which is a reflection of the character of the Indonesian people. This is because open space is a place for social interaction, so that it can unite all members of society without distinguishing between social, economic, ethnic, religious and cultural backgrounds. The purpose of this paper is to determine the model of community participation in the management of Green Open Space (RTH) in Banggai Regency. The research method used in this study is empirical legal research with a sociological juridical type. The results show that the model of community participation in the management of public Green Open Space is grants to land rights, handing over private land to public Green Open Space, helping finance the development and maintenance of public Green Open Space, monitoring the use of public Green Open Space, and counseling about the role of Green Open Space